Over-Expression of Osteopontin as Potential Predictive Biomarker for Bladder Cancer Treatment - Andy Zulfiqqar; Indrawarman Soerohardjo; Sumadi Lukman Anwar (Indonesian Journal of Cancer, 2020)
Background: Current options for management of bladder cancer (BCa) still depend on traditional clinical determinants of stage and histological grade which often do not reflect the biological entity of the tumors. Therefore, new biomarkers are required to better determine suitable treatments for different types of bladder cancers. Recent research has shown osteopontin (OPN) expressions correlate with clinic-pathological variables and outcomes of bladder cancer. This study aimed to evaluate the expression of OPN in the Indonesian population, and it’s potential role as an immune-targeting therapy of BCa. Methods: Total RNAs from formalin-fixed paraffin-embedded tissues were extracted from 49 patients with bladder cancer consisting of normal histopathology (n = 4), chronic cystitis (n = 15), non-muscle-invasive bladder cancer (NMIBC, n = 15), and muscle-invasive breast cancer (MIBC, n = 15). The expression of OPN was measured using reverse transcription-polymerase chain reaction. Results: The baseline clinical and histo-pathological characteristics were not statistically different. The expression of OPN was statistically higher in bladder cancer compared to normal histology tissues (P < .001). The expression of OPN was statistically higher in MIBC compared to NMIBC (P < .001). Conclusions: The expression of OPN was significantly higher in bladder cancer and compared to NIMBC, the OPN expression in MIBC was significantly higher rendering the potential role of OPN expression as a surrogate biomarker marker to determine suitable treatment options for patients with bladder cancer.